Effects of low frequency repetitive transcranial magnetic stimulation on motor recovery in subacute stroke patients with different motor evoked potential status: a randomized controlled trial - Qian, Wenjun; Liao, Xiaoyu; Ju, Xiaowen; Gao, Yaxin; Wu, Miao; Xie, Chen; Zhang, Yaoying; Long, Xianming; Qian, Surong; Gong, Yan (Frontiers in Neurology, 2024)
Objectives To explore the effects of low-frequency repetitive transcranial magnetic stimulation (LF-rTMS) on motor function and cortical excitability in stroke patients with different motor evoked potential (MEP) status. Methods A total of 80 stroke patients were enrolled in this randomized controlled trial and divided into two groups according to MEP status (− or +) of lesioned hemisphere. Then, each group was randomly assigned to receive either active or sham LF-rTMS. In addition to conventional rehabilitation, all participants received 20 sessions of rTMS at 1 Hz frequency through the active or the sham coil over 4 weeks. Fugl-Meyer Assessment (FMA), National Institutes of Health Stroke Scale (NIHSS), Shoulder Abduction Finger Extension (SAFE) and Barthel Index (BI), bilateral resting motor threshold (rMT), amplitude of Motor evoked potential (MEP) and Central Motor Conduction Time (CMCT), and Interhemispheric asymmetry (IHA) were blindly assessed at baseline, 4 weeks and 8 weeks after treatment, respectively. Results At 4 weeks after intervention, FMA and NIHSS changed scores in 1 Hz MEP(+) group were significantly higher than those in the other three groups (p < 0.001). After receiving 1 Hz rTMS, stroke patients with MEP(+) showed significant changes in their bilateral cortical excitability (p < 0.05). At 8 weeks after intervention, 1 Hz MEP(+) group experienced higher changes in NIHSS, FMA, SAFE, and BI scores than other groups (p < 0.001). Furthermore, 1 Hz rTMS intervention could decrease unaffected cortical excitability and enhance affected cortical excitability of stroke patients with MEP(+) (p < 0.05). The correlation analysis revealed that FMA motor change score was associated with decreased unaffected MEP amplitude (r = −0.401, p = 0.010) and decreased affected rMT (r = −0.584, p < 0.001) from baseline, which was only observed in the MEP(+) group. Conclusion The effects of LF-rTMS on motor recovery and cortical excitability were more effective in stroke patients with MEP than those with no MEP.